A series of dysprosium clusters assembled by a substitution effect-driven out-to-in growth mechanism. Issue 8 (8th March 2021) - Wang, Hai-Ling; Liu, Tong; Zhu, Zhong-Hong; Peng, Jin-Mei; Zou, Hua-Hong; Liang, Fu-Pei
Abstract : The diacylhydrazone ligands with different substituents were reacted with Dy(NO3 )3 ·6H2 O to obtain 16 nuclear (1 ) and 10 nuclear (2 ) and pentanuclear (3 ) dysprosium clusters. Clusters 1–3 are gradually formed through out-to-in growth mechanism. Abstract : Although the design and synthesis of high-nuclear lanthanide clusters with specific shapes and functions have been an active area of research, effective experience and rules to guide further systematic expansion of lanthanide clusters with different connections are lacking. Herein, we adjusted the steric hindrance effects on the substituents of diacylhydrazone ligands (H4 L 1, N ′ 2, N ′ 9 -bis(( E )-2-hydroxybenzylidene)-1, 10-phenanthroline-2, 9-dicarbohydrazide; H4 L 2, N ′ 2, N ′ 9 -bis(( E )-2-hydroxy-3-methylbenzylidene)-1, 10-phenanthroline-2, 9-dicarbohydrazide; H4 L 3, N ′ 2, N ′ 9 -bis(( E )-3-( tert -butyl)-2-hydroxybenzylidene)-1, 10-phenanthroline-2, 9-dicarbohydrazide) and reacted them with Dy(NO3 )3 ·6H2 O under solvothermal conditions to obtain three dysprosium clusters (1–3 ) with different shapes. The molecular formulas of the abovementioned clusters are [Dy16 (L 1 )3 (μ3 -OH)25 (NO3 )11 (H2 O)10 ]·4CH3 CN·8CH3 OH, [Dy10 (L 2 )4 (μ2 -OH)2 (μ3 -O)4 (NO3 )4 (CH3 CN)2 (CH3 OH)4 (H2 O)8 ]·CH3 OH·8H2 O, and [Dy5 (L 3 )2 (μ2 -CH3 O)(μ2 -OH)2 (μ4 -O)(NO3 )2 (CH3 OH)2 ]·6CH3 OH·2CH3 CN. Cluster 1 with a brucite-like planar structure crystallizes in the P 21 / n space group of the monoclinic system. The Dy(iii ) ions in the cluster 1 structure are bridged by μ3 -OH − to form a plane triangle shape. In addition, the structure of cluster 1 contains three layers of Dy(iii ) ions (1 + 6 + 9) with different coordination environments. Cluster 2 crystallizes in the P 1̄ space group of the triclinic system. The cluster core in cluster 2 is composed of two molecules of missing cubane Dy4 O6 and two Dy(iii ) ions. The ligand (L 2 ) 4− adopts two coordination modes (μ3 -η 1 :η 1 :η 2 :η 1 :η 1 :η 2 :η 1 :η 1 and μ5 -η 2 :η 1 :η 1 :η 1 :η 1 :η 1 :η 1 :η 1 :η 1 :η 2 ) to chelate Dy(iii ) ions. In addition, Dy(iii ) ions in Dy4 O6 are connected by μ2 -OH − and μ3 -OH − . Two molecules of planar Dy3 L 3 intersect to form cluster 3, and it crystallizes in the I 2/ a space group of the monoclinic system. The analysis of the structure of clusters 1–3 shows that they are formed by a stepwise assembly process from outside to inside. To the best of our knowledge, a very small number of examples have reported that a series of differently connected dysprosium clusters were obtained through the regulation of substitution effects. Notably, we are the first to propose the out-to-in growth mechanism of planar high-nucleus dysprosium clusters. The results of the variable temperature AC susceptibility test show that clusters 1, 2, and 3 exhibit single-molecule magnet-like behavior under zero-field conditions.